Active Shielding of Power Frequency Magnetic Field in Buildings in the Vicinity of the Electric Airlines - Kuznetsov B.I.; Nikitina T.B.; Bovdui I.V. (Problems of the Regional Energetics, 2019)
The purpose of the work is the development of the method for the synthesis of a robust feed-forward active shielding system of the magnetic field, generated by high voltage power lines for reducing the initial magnetic field induction to the sanitary standards level and decreasing the system sensitivity to the plant parameters’ variations. This work is devoted to the solution of a multicriterion stochastic game, in which the vector payoff is calculated based on the Maxwell equations solutions in the quasi-stationary approximation. The multicriterion game solution depends on the multiswarm particles optimization algorithms. The initial parameters for the synthesis of the active shielding system are the location of the high voltage power lines with respect to the protected from transmission line space, geometry and number of buses, operating currents, as well as the size of the protected space and magnetic field induction normative value. The aim is achieved by determination of the number, configuration, spatial arrangement, and currents in compensation coils, setting algorithm of the robust feed-forward active shielding system of the magnetic field, as well as the resulting value of the induction magnetic field at the points of the protected space. New scientific results of the theoretical and field experimental researches of the effectiveness of a single circuit active shielding system with a single compensation coil are carried out. The possibility of reduction of the initial magnetic field induction level is obtained. It is shown that the experimental and calculated magnetic field induction values differ up to 20 %.